Strike Settlement and Economic Activity : An Empirical Analysis - Swidinsky, R. (Relations industrielles / Industrial Relations, 1976)
This paper explores the relationship between the outcome of strike and the level of economic activity. The findings are based on Canadian data for the period 1901-1953.